CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with maze-shaped wrinkle structure and preparation method of CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor

By constructing a CNTs-COOH/MXene conductive network with a maze-shaped fold structure on the TPU fiber membrane, the shortcomings of traditional sensors in high sensitivity and large strain range applications are solved, and flexible strain sensors with higher sensitivity and larger strain range are achieved , suitable for applications in various fields.

CN119468897APending Publication Date: 2025-02-18LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597115.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional sensors are difficult to meet the needs of high sensitivity and large strain range in the fields of marine exploration, medical diagnosis, bioengineering, etc., especially when applied to human surfaces, traditional sensors lack breathability and wear comfort.

Method used

The CNTs-COOH/MXene/TPU fiber membrane with a maze-shaped pleated structure is used as the base material of the flexible strain sensor. The conductive network is built through steps such as swelling, suction filtration, retraction and packaging to improve the sensitivity and strain range of the sensor.

Benefits of technology

It achieves higher sensitivity, greater strain range and better wear comfort, and is suitable for electronic skin, medical diagnosis and human-computer interaction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119468897A_ABST
    Figure CN119468897A_ABST
Patent Text Reader

Abstract

The invention discloses a CNTs-COOH / MXene / TPU (Thermoplastic Polyurethane) fiber membrane flexible strain sensor with a labyrinth-shaped wrinkle structure and a preparation method of the CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor. And washing and drying the TPU fiber membrane, soaking the TPU fiber membrane in chloroform (CHCl3), and then fixing and drying the TPU fiber membrane by using a mold. And carrying out vacuum suction filtration on the CNTs-COOH / MXene mixed solution dispersed in the N, N-dimethylformamide (DMF) and deionized water mixed solution by using a suction filtration device, so that the CNTs-COOH / MXene composite nanomaterial is attached to the TPU fiber membrane, and finally, removing the mold, so that the TPU fiber membrane retracts. Along with the retraction of the fiber membrane substrate, a CNTs-COOH / MXene micro-wrinkle structure is formed on the surface of the fiber membrane substrate. According to the structure, the strain range of the sensor can be increased, and the sensitivity can be improved through wrinkle deformation and microcrack generation under different strain conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensors, and in particular relates to a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure and a preparation method thereof. Background Art

[0002] In recent years, many intelligent detection devices are equipped with a variety of sensors, which have demonstrated their practicality in various fields such as marine exploration, medical diagnosis, bioengineering, and smart home. The progress of the information age has given people higher expectations for sensors, but traditional sensors can no longer meet people's actual needs, so flexible strain sensors have developed rapidly. Strain sensors based on TPU fiber membranes have become a current research hotspot due to their excellent flexibility, good air permeability, resilience, comfort, and the ability to achieve large-scale production. Summary of the invention

[0003] The flexible strain sensor developed by the present invention has the characteristics of being more breathable and comfortable to wear. At the same time, the TPU fiber membrane provides sufficient space and attachment points for the embedding and combination of the conductive material, forming a good conductive network, so that the sensor has a higher sensitivity and a larger strain range of sensing performance.

[0004] The technical solution adopted by the present invention is: a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure, which uses TPU fiber membrane as a base material and CNTs-COOH / MXene as a conductive material, and is obtained by swelling, filtration, shrinkage and packaging.

[0005] A CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure, characterized in that the preparation method is carried out according to the following steps:

[0006] Step 1, uniformly dispersing the diluted MXene solution and CNTs-COOH solution in DMF by ultrasonication to obtain a CNTs-COOH / MXene mixed solution;

[0007] Step 2: Wash and dry the TPU fiber membrane as an elastic substrate, put it into a CHCl3 solution to swell it, and then fix it with a mold;

[0008] Step 3: Use a suction filtration device to vacuum filter the CNTs-COOH / MXene mixed solution to make the conductive coating evenly adhere to the TPU fiber membrane to obtain a CNTs-COOH / MXene / TPU fiber membrane;

[0009] Step 4: releasing the mold to allow the fiber membrane to slowly retract, thereby obtaining a fiber membrane with maze-shaped folds;

[0010] Step 5: bonding the copper electrode and the maze-shaped wrinkled fiber membrane with conductive silver paste, and then curing;

[0011] Step 6: Encapsulate the labyrinth-shaped corrugated fiber membrane equipped with electrodes with PDMS to obtain a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a labyrinth-shaped corrugated structure.

[0012] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that, in step one, the CNTs-COOH / MXene mixed solution is achieved by the following steps: taking 0.1 mg / ml CNTs-COOH aqueous solution and 10 mg / ml MXene aqueous solution, adding 4 to 6 ml DMF thereto, and performing an ultrasonic process to uniformly disperse CNTs-COOH and MXene therein to obtain a mixed solution with a concentration of 5.1 mg / ml.

[0013] The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure is characterized in that the specific preparation method of the CNTs-COOH / MXene mixed solution is as follows:

[0014] Step 1.1: MXene can be obtained through chemical etching and ultrasonic stripping. During the chemical etching reaction, lithium fluoride LiF is added to a polytetrafluoroethylene beaker, and then hydrochloric acid HCl is added, heated in a water bath and stirred to make them fully react. In this process, titanium aluminum carbide Ti3AlC2 needs to be added to the polytetrafluoroethylene beaker in small amounts and multiple times, and then sealed, and continued to be stirred in a constant temperature water bath. After the etching reaction is completed, the supernatant of the solution after centrifugation is poured out, and then acid washing is performed, and the unreacted LiF reaction is removed with hydrochloric acid HCl, and then washed with water, and the solution is centrifuged several times with deionized water to neutrality, and finally ultrasonic stripping is performed under gas protection conditions, nitrogen is passed into the solution to discharge the air in the bottle, and then it is sealed, ultrasonic stripping is performed for 0.5 to 1.5 hours, and finally centrifuged again. The upper layer of liquid obtained is the MXene solution;

[0015] Step 1.2: dilute the MXene solution to a concentration of 10 mg / ml and ultrasonicate for 3 to 7 minutes to obtain a MXene colloidal solution;

[0016] Step 1.3: Add 4-6 ml CNTs-COOH to deionized water and sonicate for 25-35 min to obtain a 0.1 mg / ml CNTs-COOH colloidal solution;

[0017] Step 1.4: Mix equal volumes of 0.1 mg / ml CNTs-COOH colloidal solution, 10 mg / ml MXene colloidal solution and a certain amount of DMF and sonicate for 25 to 35 min to uniformly disperse CNTs-COOH and MXene therein to obtain a CNTs-COOH / MXene mixed solution with a concentration of 5.1 mg / ml.

[0018] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that, in step 1.1, the temperature is maintained at 35-45°C during the water bath heating and stirring process, and titanium aluminum carbide is slowly added in 20 times, and this process lasts for 20-30 minutes.

[0019] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that in step 1.1, the gas flow rate of the nitrogen introduction process is 20 to 25 m / s, and the time is 0.5 to 1.5 h.

[0020] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that in step 1.2, the ultrasonic power is 5 to 15 W; in step 1.3, the ultrasonic power is 40 to 60 W; in step 1.4, the ultrasonic power is 40 to 60 W.

[0021] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that, in step 2, the swelling of the TPU fiber membrane is achieved by the following steps: the cleaned and dried TPU fiber membrane is soaked in CHCl3 for 5 to 10 minutes, then fixed with a mold, and dried at room temperature for 10 to 15 minutes to obtain a swollen fiber membrane.

[0022] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that, in step three, the filtration process is achieved by the following steps: taking 2.5 ml of a CNTs-COOH / MXene mixed solution with a concentration of 5.1 mg / ml and vacuum filtering to obtain a CNTs-COOH / MXene / TPU fiber membrane.

[0023] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure is characterized in that, in step five, the assembly of the conductive silver paste is achieved by the following steps: the conductive silver paste is evenly applied on both sides of the fiber membrane so that it wraps a fiber membrane with a length of 0.2 cm and a width of 0.5 cm, and then dried and cured at 50-70°C.

[0024] The above-mentioned CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped corrugated structure is characterized in that, in step six, the PDMS encapsulation is achieved by the following steps: the fiber membrane sensing area equipped with electrodes is immersed in a mixed solution of PDMS prepolymer and curing agent with a mass ratio of 10:1 for 25 to 35 seconds, and then cured at 50 to 70°C for 3 to 5 hours to obtain a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped corrugated structure.

[0025] The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped pleated structure provided by the present invention can be applied to electronic skin, medical diagnosis, human-computer interaction and other fields.

[0026] Compared with the prior art, the present invention has the following beneficial technical effects:

[0027] 1. The present invention constructs a maze-shaped pleated structure on the surface of the fiber membrane by swelling and fixing the fiber membrane, attaching a conductive material, and then shrinking it. This structure helps to increase the strain range of the flexible strain sensor. The overall preparation process is simple and there are no complicated operating steps.

[0028] 2. The present invention is a flexible strain sensor that converts external stimuli into electrical signals based on changes in the internal conductive network.

[0029] 3. The preparation method of the present invention enables the strain sensor to have a wider sensing range, higher sensitivity, and a stable cyclic conductive response.

[0030] 4. The fiber membrane flexible strain sensor prepared by the present invention is more breathable and comfortable to wear. It can be attached to the surface of the human body to detect human body movements and physiological signals in real time. It can be widely used in electronic skin, medical diagnosis, human-computer interaction and other fields. At the same time, the two-dimensional TPU fiber membrane provides sufficient space and attachment points for the embedding and combination of conductive materials to form a good conductive network. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD diagram of the raw material Ti3AlC2 and the prepared single-layer MXene nanosheet in Example 1.

[0032] Figure 2 Schematic diagram of the sensitivity and strain range of the fiber membrane flexible strain sensor with a maze-shaped pleated structure prepared in Example 1.

[0033] Figure 3 This is a SEM image of the overall attachment morphology of the fiber membrane of the fiber membrane flexible strain sensor with a maze-shaped pleated structure in Example 1.

[0034] Figure 4 This is a SEM image of the maze-shaped wrinkle morphology of the fiber membrane of the fiber membrane flexible strain sensor with a maze-shaped wrinkle structure in Example 1. DETAILED DESCRIPTION

[0035] Example 1

[0036] (I) The preparation method of the fiber membrane flexible strain sensor with a maze-shaped fold structure is as follows:

[0037] 1. MXene can be obtained through chemical etching and ultrasonic stripping. During the chemical etching reaction, LiF is added to a polytetrafluoroethylene beaker, and then HCl is added. The beaker is heated in a water bath at 35-45°C and stirred to make them fully react. In this process, Ti3AlC2 needs to be added to the polytetrafluoroethylene beaker in small amounts for about 20 times in 20-30 minutes, and then sealed. Continue to stir in a constant temperature water bath. When the etching reaction is completed, pour out the supernatant of the centrifuged solution. Then pickle it and remove the unreacted LiF reaction with HCl. Then wash it with water and centrifuge the solution several times with deionized water until it is neutral. Finally, ultrasonic stripping is performed under gas protection conditions, and nitrogen with a flow rate of 20-25m / s is passed into the solution to discharge the air in the bottle. The process lasts for 0.5-1.5h. Then seal it and ultrasonic strip it for 1h. Finally, centrifuge it again, and the upper layer of liquid obtained is the MXene solution.

[0038] 2. Dilute the MXene solution to a concentration of 10 mg / ml and ultrasonicate at a power of 5 to 15 W for 3 to 7 min to obtain a MXene colloidal solution.

[0039] 3. Add a certain amount of CNTs-COOH to deionized water and ultrasonicate for 25 to 35 minutes at a power of 40 to 60 W to obtain a 0.1 mg / ml CNTs-COOH colloidal solution.

[0040] 4. Mix equal volumes of the 10 mg / ml MXene colloidal solution and 0.1 mg / ml CNTs-COOH obtained in steps 2 and 3, add 4-6 ml DMF, and ultrasonicate at a power of 40-60 W for 25-35 min to uniformly disperse MXene and CNTs-COOH therein to obtain a CNTs-COOH / MXene mixed solution with a concentration of 5.1 mg / ml.

[0041] 5. The TPU fiber membrane is cleaned and dried as an elastic substrate, and then immersed in a CHCl3 solution for 5 to 10 minutes, fixed with a mold, and then dried at room temperature for 10 to 15 minutes to obtain a swollen fiber membrane.

[0042] 6. Take 2.5 ml of the CNTs-COOH / MXene mixed solution obtained in step 4 and use a suction filtration device to perform vacuum filtration to make the conductive coating evenly adhere to the TPU fiber membrane obtained in step 5 to obtain a CNTs-COOH / MXene / TPU fiber membrane.

[0043] 7. Release the mold of the CNTs-COOH / MXene / TPU fiber membrane obtained in step 6, and allow the fiber membrane to slowly shrink to obtain a CNTs-COOH / MXene / TPU fiber membrane with a maze-shaped pleated structure.

[0044] 8. The conductive silver paste is evenly applied on both sides of the CNTs-COOH / MXene / TPU fiber membrane with a maze-shaped pleated structure obtained in step 7, so that it wraps a fiber membrane with a length of 0.2 cm and a width of 0.5 cm, and then dried and cured at 50-70°C to obtain a fiber membrane equipped with electrodes.

[0045] 9. The fiber membrane sensing area equipped with electrodes obtained in step 8 is immersed in a mixed solution of PDMS prepolymer and curing agent with a mass ratio of 10:1 for 25 to 35 seconds, and then cured at 50 to 70°C for 3 to 5 hours to obtain a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure.

[0046] (II) Characterization

[0047] Figure 1 XRD patterns of raw material Ti3AlC2 and prepared single-layer MXene nanomaterials. Figure 1 The results show that the present invention successfully prepared MXene nanosheets.

[0048] Figure 1 The XRD diagram of the raw material Ti3AlC2 and the prepared single-layer MXene nanomaterial in Example 1. The crystal structures of Ti3AlC2 and MXene were analyzed respectively. By comparing the XRD spectra of MXene and Ti3AlC2, it can be found that the diffraction peak of the (104) crystal plane disappears at 38.85° in the XRD spectrum of MXene, which proves that the Al element of the MAX phase is selectively etched by hydrofluoric acid, and the (002) crystal plane moves forward from 9.4° to 5.7°, indicating that the interlayer spacing of MXene increases and is successfully peeled off into a single-layer MXene nanosheet.

[0049] Figure 2 The strain sensing characteristics of the CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped fold structure prepared in Example 1. A digital multimeter was used to test the real-time change of the resistance of the fiber membrane with strain. The strain range of the CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped fold structure is 0-190%. In the strain range of 0-80%, GF=63.3, in the strain range of 80-140%, GF=948.7, and in the strain range of 140-190%, GF=23640.4.

[0050] Figure 3 This is a SEM image of the overall attachment morphology of the fiber membrane of the fiber membrane flexible strain sensor with a maze-shaped pleated structure in Example 1. Figure 4 This is a SEM image of the labyrinth-shaped wrinkle morphology of the fiber membrane of the fiber membrane flexible strain sensor with a labyrinth-shaped wrinkle structure in Example 1. The surface micromorphology of the fiber was characterized using a scanning electron microscope. Figure 3 It can be clearly seen that CNTs-COOH / MXene is uniformly attached to the surface of the fiber membrane. Figure 4 It can be clearly seen that a maze-shaped wrinkled structure is formed on the surface of the fiber membrane.

Claims

1. A CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure, characterized in that: The preparation method is carried out according to the following steps: Step 1, uniformly dispersing the diluted MXene solution and CNTs-COOH solution in DMF by ultrasonication to obtain a CNTs-COOH / MXene mixed solution; Step 2: Wash and dry the TPU fiber membrane as an elastic substrate, put it into a CHCl3 solution to swell it, and then fix it with a mold; Step 3: Use a suction filtration device to vacuum filter the CNTs-COOH / MXene mixed solution to make the conductive coating evenly adhere to the TPU fiber membrane to obtain a CNTs-COOH / MXene / TPU fiber membrane; Step 4: releasing the mold to allow the fiber membrane to slowly retract, thereby obtaining a fiber membrane with maze-shaped folds; Step 5: bonding the copper electrode and the maze-shaped wrinkled fiber membrane with conductive silver paste, and then curing; Step 6: Encapsulate the labyrinth-shaped corrugated fiber membrane equipped with electrodes with PDMS to obtain a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a labyrinth-shaped corrugated structure.

2. According to claim 1, a CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure is characterized in that: In step 1, the CNTs-COOH / MXene mixed solution is achieved by the following steps: taking a 0.1 mg / ml CNTs-COOH aqueous solution and a 10 mg / ml MXene aqueous solution, adding 4 to 6 ml of DMF thereto, and performing an ultrasonic process to uniformly disperse CNTs-COOH and MXene therein to obtain a mixed solution with a concentration of 5.1 mg / ml.

3. According to claim 2, a CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure is characterized in that: The specific preparation method of CNTs-COOH / MXene mixed solution is as follows: Step 1.1: MXene can be obtained through chemical etching and ultrasonic stripping. During the chemical etching reaction, lithium fluoride LiF is added to a polytetrafluoroethylene beaker, and then hydrochloric acid HCl is added, heated in a water bath and stirred to make them fully react. In this process, titanium aluminum carbide Ti3AlC2 needs to be added to the polytetrafluoroethylene beaker in small amounts and multiple times, and then sealed, and continued to be stirred in a constant temperature water bath. After the etching reaction is completed, the supernatant of the solution after centrifugation is poured out, and then acid washing is performed, and the unreacted LiF reaction is removed with hydrochloric acid HCl, and then washed with water, and the solution is centrifuged several times with deionized water to neutrality, and finally ultrasonic stripping is performed under gas protection conditions, nitrogen is passed into the solution to discharge the air in the bottle, and then it is sealed, ultrasonic stripping is performed for 0.5 to 1.5 hours, and finally centrifuged again. The upper layer of liquid obtained is the MXene solution; Step 1.2: dilute the MXene solution to a concentration of 10 mg / ml and ultrasonicate for 3 to 7 minutes to obtain a MXene colloidal solution; Step 1.3: Add 4-6 ml CNTs-COOH to deionized water and sonicate for 25-35 min to obtain a 0.1 mg / ml CNTs-COOH colloidal solution; Step 1.4: Mix equal volumes of 0.1 mg / ml CNTs-COOH colloidal solution, 10 mg / ml MXene colloidal solution and a certain amount of DMF and sonicate for 25 to 35 min to uniformly disperse CNTs-COOH and MXene therein to obtain a CNTs-COOH / MXene mixed solution with a concentration of 5.1 mg / ml.

4. According to claim 3, a CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure is characterized in that: In step 1.1, the temperature is maintained at 35-45° C. during the water bath heating and stirring process, and titanium aluminum carbide is slowly added in 20 portions, and this process lasts for 20-30 minutes.

5. According to claim 3, a CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped pleated structure is characterized in that: In step 1.1, the gas flow rate of the nitrogen introduction process is 20-25 m / s, and the time is 0.5-1.5 h.

6. According to claim 3, a CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure is characterized in that: In step 1.2, the ultrasonic power is 5 to 15 W; in step 1.3, the ultrasonic power is 40 to 60 W; in step 1.4, the ultrasonic power is 40 to 60 W.

7. The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure according to claim 1, characterized in that: In step 2, the swelling of the TPU fiber membrane is achieved by the following steps: the cleaned and dried TPU fiber membrane is immersed in CHCl3 for 5 to 10 minutes, then fixed with a mold, and dried at room temperature for 10 to 15 minutes to obtain a swollen fiber membrane.

8. The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure according to claim 1, characterized in that: In step three, the filtration process is achieved by the following steps: 2.5 ml of a CNTs-COOH / MXene mixed solution with a concentration of 5.1 mg / ml is taken and vacuum filtered to obtain a CNTs-COOH / MXene / TPU fiber membrane.

9. The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped pleated structure according to claim 1, characterized in that: In step five, the conductive silver paste is assembled by the following steps: the conductive silver paste is evenly applied on both sides of the fiber membrane to wrap the fiber membrane with a length of 0.2 cm and a width of 0.5 cm, and then dried and cured at 50-70°C.

10. The CNTs-COOH / MXene / TPU fiber film flexible strain sensor with a maze-shaped fold structure according to claim 1, characterized in that: In step six, the PDMS encapsulation is achieved by the following steps: immersing the fiber membrane sensing area equipped with electrodes in a mixed solution of PDMS prepolymer and curing agent with a mass ratio of 10:1 for 25 to 35 seconds, and then curing it at 50 to 70°C for 3 to 5 hours to obtain a CNTs-COOH / MXene / TPU fiber membrane flexible strain sensor with a maze-shaped pleated structure.